2019
DOI: 10.1111/1742-6723.13411
|View full text |Cite
|
Sign up to set email alerts
|

Risk variables associated with abnormal calcium, magnesium and phosphate levels among emergency department patients

Abstract: Objective The utility of calcium, magnesium and phosphate measurement in the ED is limited. We aimed to determine clinical risk variables for abnormal levels of these electrolytes in order to inform the development of an ordering guideline. Methods We performed a retrospective, observational study of patients who presented to a tertiary referral ED between January and June 2017. Adult patients who had serum calcium, magnesium or phosphate tests completed during their ED stay were included. Presenting symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Some risk factors differ between our studies, but corroborate with the following: chemotherapy (stated as anti-neoplastic medication in our study) for hypocalcemia, diabetes for hypomagnesemia, chronic kidney disease for hypermagnesemia and hyperphosphatemia and seizure for hypophosphatemia. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some risk factors differ between our studies, but corroborate with the following: chemotherapy (stated as anti-neoplastic medication in our study) for hypocalcemia, diabetes for hypomagnesemia, chronic kidney disease for hypermagnesemia and hyperphosphatemia and seizure for hypophosphatemia. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Some risk factors differ between our studies, but corroborate with the following: chemotherapy (stated as antineoplastic medication in our study) for hypocalcemia, diabetes for hypomagnesemia, chronic kidney disease for hypermagnesemia and hyperphosphatemia and seizure for hypophosphatemia. 19 In 2013, Lindner et al published their work on the demographic and clinical characteristics of hypercalcemia in the ED. Their retrospective cohort study included 14,984 patients for whom serum calcium levels had been electively drawn by ED physicians.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 In patients with severe food intolerance and concomitant proton pump inhibitor usage, evaluation should include testing for magnesium and calcium deficiency. 12 Patients often have higher depression and anxiety scores, as well as a lower physical quality of life, and medical teams sometimes neglect the patients' psychological state. 13 It is imperative that the multidisciplinary team recognize and acknowledge the patients psychological comorbidities and engage expertise to manage them.…”
Section: Comorbid Illness Associated With Complications: Best Practice Advicementioning
confidence: 99%
“…Variants of the TRPM6 gene-another TRP channel belonging to subfamily M, which is a close homolog of TRPM7 [31]-caused hypomagnesaemia accompanied by seizures [32]. Two recent studies did not find seizures as a significant risk factor for hypomagnesaemia [33,34], but seizures are among the neurological symptoms that may occur in those with severe hypomagnesaemia [35,36]. A meta-analysis of 40 studies showed that the serum magnesium concentrations were not different between epilepsy patients and control subjects, but hair magnesium concentrations were lower in both treated and non-treated patients compared to controls.…”
Section: Introductionmentioning
confidence: 99%